2012
DOI: 10.4103/0973-1296.103650
|View full text |Cite
|
Sign up to set email alerts
|

Antipsoriatic activity and cytotoxicity of ethanolic extract of Nigella sativa seeds

Abstract: Background:Nigella sativa Linn (Ranunculaceae) is popularly known as black cumin with a wide spectrum of pharmacological activities including anti-inflammatory, antibacterial, antifungal and antihelmenthic. The seeds are externally applied for eruptions of skin. The seeds are used traditionally for psoriasis tropicus with general pain and eruption of patches.Objective:The ethanolic extract of Nigella sativa seeds were evaluated for antipsoriatic activity.Materials and Methods:The screening of antipsoriatic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…sativa widely use evidence showed its anti-inflammatory effect is comparable effect of of 100 mg/kg aspirin by its inhibitory effects on Carrageenan induced paw edema [28]. Also, evidences show N. sativa anti-inflammatory therapeutic effects on psoriasis (by produced the ethanolic extract) [29], Acne vulgaris (as an oil lotion 10% significantly reduced mean lesion count of and pustules after 2 months of therapy) [30, 31], Vitiligo (by Lyophilized seed extract of N. sativa and its active ingredient) [32, 33], Hypersensitivity reactions (by using carbonyl fraction of N. sativa and its active components, thymoquinone and nigellone) [34, 35] and Skin cancers (by enhancement of the natural killer (NK) cell in anti-cancer program) [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…sativa widely use evidence showed its anti-inflammatory effect is comparable effect of of 100 mg/kg aspirin by its inhibitory effects on Carrageenan induced paw edema [28]. Also, evidences show N. sativa anti-inflammatory therapeutic effects on psoriasis (by produced the ethanolic extract) [29], Acne vulgaris (as an oil lotion 10% significantly reduced mean lesion count of and pustules after 2 months of therapy) [30, 31], Vitiligo (by Lyophilized seed extract of N. sativa and its active ingredient) [32, 33], Hypersensitivity reactions (by using carbonyl fraction of N. sativa and its active components, thymoquinone and nigellone) [34, 35] and Skin cancers (by enhancement of the natural killer (NK) cell in anti-cancer program) [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric attenuates the inflammatory response by down regulating the activities of nitric oxide synthase, lipoxygenase, and cyclooxygenase-2 [8] . On the other hand, black cumin might possess immune-stimulatory, anti-inflammatory [9] , and antiallergic [10] effects. Turmeric and black cumin caused complete recovery and totally decreased pruritus scores in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that orthokeratosis was five times higher after topical application of the ethanolic extract when compared with a placebo control, which was nearly equivalent to the positive control tazarotene (0.1%) gel. The antiproliferant activity of the ethanolic extract of Nigella sativa was accepted and comparable to that of the positive control, asiaticoside [ 66 ].…”
Section: Essential Oils/botanical Agents-based Advanced Nano-delivery...mentioning
confidence: 99%